We Are Now a Nation : Croats Between 'Home and Homeland' - Winland, Daphne N., 1957- (Book collections on Project MUSE., 2007)
The Yugoslav War of Succession had untold ramifications for those living in the embattled region. What often goes overlooked, however, is the impact that the war had on people from the former Yugoslavia who were living abroad. We are Now a Nation considers the effect that the war and the independence of Croatia had on Croatian diaspora-homeland relations. In doing so, it confronts complex questions of ideology, nostalgia, social suffering, nationalism, and identity politics as manifested in the relationship between diaspora and homeland Croats.Daphne Winland draws upon extensive, multi-sited ethnographic research in both Toronto and Croatia from 1992 to the present, exploring the problematic nature of Croatian identity. The occasion of Croatian independence, she suggests, resulted in the emergence of a politics of 'desire' and 'disdain,' which further complicated efforts to define 'Croatness' (Hrvatstvo) both at home and abroad. The idea of the Croatian homeland has become, therefore, an ambiguous space of identification, a source of either conflict and tension or unity and pride, a place to remember, to forget, or to return to.The first book-length examination of North American Croatian diaspora responses to war and independence, We are Now a Nation highlights the contradictions and paradoxes of contemporary debates about identity, politics, and place.